2021
DOI: 10.1002/brb3.2243
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional changes in patients with Crohn's disease: A resting‐state fMRI study

Abstract: contributed to the work equally and should be regarded as co-first authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Similar changes were found for ulcerative colitis (25). In inactive CD patients, the ReHo values in the superior frontal gyrus, putamen, anterior cingulate and supplementary motor areas were altered in other study (15,26,27). In addition, Bao et al found that the gray matter volumes in CD patients were changed in that brain region (8), which suggested that CD patients have abnormal brain activity and morphology.…”
Section: Discussionmentioning
confidence: 90%
“…Similar changes were found for ulcerative colitis (25). In inactive CD patients, the ReHo values in the superior frontal gyrus, putamen, anterior cingulate and supplementary motor areas were altered in other study (15,26,27). In addition, Bao et al found that the gray matter volumes in CD patients were changed in that brain region (8), which suggested that CD patients have abnormal brain activity and morphology.…”
Section: Discussionmentioning
confidence: 90%
“…Both postcentral and precentral gyri are involved in pain processing, which is a multidimensional experience involving sensory discrimination, cognition evaluation, and affective motivation [30]. A large number of researches have proven the essential roles of the postcentral and precentral gyri in chronic pain-related [17,18,31]. Therefore, we hold the opinion that the decreased neural activity in the postcentral and precentral gyri may be associated with angina pectoris.…”
Section: Disease Markersmentioning
confidence: 96%
“…In contrast with the amplitude of low-frequency fluctuations (ALFF), fALFF can effectively suppress physiological noise, decrease interference with cerebrospinal fluid, and show high sensitivity to detect spontaneous neural activity [16]. In recent years, ALFF and fALFF analyses have been widely applied in a series of neuropsychiatric disorders and have been used in the research on pain mechanisms, showing abnormalities of neural activity in pain-related diseases such as Crohn's disease, irritable bowel syndrome, and chronic low back pain [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating the amplitude of the BOLD signal relative to the baseline, ALFF analysis can reflect the degree of spontaneous activity of each voxel in the brain. In various brain regions of CD patients, including the insula, anterior cingulate gyrus, medial prefrontal cortex, precentral gyrus, secondary somatosensory cortex, and hippocampus cortex, studies have revealed that the ALFF values are different (34). The regulation of visceral sensation (pain) and movement is controlled by these brain regions, which are all parts of the visceral sensation and pain network.…”
Section: Alff Analysismentioning
confidence: 99%